Pengaruh Hutan Mangrove Terhadap Produksi Udang Windu (Penaeus monodon) Pada Tambak Silvofishery di Desa Tanjung Ibus Kecamatan Secanggang Kabupaten Langkat - ZAINURI SYAM; Yunasfi Djayus; MARAGUNUNG DALIMUNTHE (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
The purpose of this research was to determine the effect of mangrove forests with different densities to the production of tiger shrimp and the factor effect were production of tiger shrimp in silvofishery pond. This study conducted in silvofishery pond in Tanjung Ibus village, Sub-district Secanggang, District of Langkat on Mei untilt October 2013, by using 2 research stations. Pond 1 was a pond with high density, and pond 2 was a pond with low density. Mangrove vegetation analysis has been done by measuring the density of seedlings, saplings and tree in each research station. Water quality and plankton sampling performed at each pond in 2 station at the inlet and the center of the pond. Sampling has been done 4 times, when the fry will bes tocked, two-month preservation period, four-month preservation period and five-month preservation period. tiger shrimp production data obtained from direct observations during the harvesting process. Mangrove density in ponds 1 for seedlings was 202 ind/ha, saplings 111 ind/ha, and tree level 958 ind/ha. Mangrove density in ponds 2 for seedlings was 56 ind/ha, saplings 272 ind/ha, and tree level 47 ind/ha. The water quality in pond 1 in general of the criteria for the aquaculture tiger shrimp be based on The Decision Minister of Marine and Fisheries No : 28 in 2004. Abundance of plankton in the pond 2 was higher than the pond 1. Tiger shrimp production in pond 1 was 42 kg, and in pond 2 was 29 kg.Keyword : Mangrove, Plankton, Silvofishery, Tiger shrimp, Water quality.